Optimization and Realization of Productive Waqf Implementation Through Cash Waqf Linked Sukuk (CWLS) SW001 Scheme at Achmad Wardi Eye Hospital - Mutaqin, Enjen Zaenal; Guntoro, Dwi (Badan Wakaf Indonesia, 2023)
Waqf is a form of religious worship that has a socio-economic dimension. The implementation of waqf which continues to experience development and progress in managing and developing its assets has led waqf to become an investment instrument that has high production values ​​in achieving community welfare. This research aims to determine the optimization and realization of the implementation of productive waqf through the CWLS SW001 in the development of retina and glaucoma centers in hospitals. Ahmad Ward's eyes. This study uses the library study method, in which researchers analyze data and information sourced from scientific journals, books, mass media, the internet and other sources related to productive waqf material and the implementation of productive waqf through the CWLS SW001 scheme. Based on the results of the analysis of data and information that the authors obtained, the authors concluded that CWLS SW001 is a productive waqf concept scheme in the form of money which is then invested in the form of Sukuk in SBSN. Where from the yield on the investment in the Sukuk, discounts and coupons were obtained which were used for the construction of a retina and glaucoma centre at the hospital. Ahmad Ward's eyes. Keywords: productive waqf; sukuk; SBSN; CWLS SW0001; retina and glaucoma centre.